Clinical utility and prognostic value of left atrial volume assessment by cardiovascular magnetic resonance in non‐ischaemic dilated cardiomyopathy. (June 2013) - Gulati, Ankur; Ismail, Tevfik F.; Jabbour, Andrew; Ismail, Nizar A.; Morarji, Kishen; Ali, Aamir; Raza, Sadaf; Khwaja, Jahanzaib; Brown, Tristan D.H.; Liodakis, Emmanouil; Baksi, Arun J.; Shakur, Rameen; et al.
<x xml:space="preserve">Abstract</x> Aims Echocardiographic studies have shown that left atrial volume (LAV) predicts adverse outcome in small heart failure (HF) cohorts of mixed aetiology. However, the prognostic value of LAV in non‐ischaemic dilated cardiomyopathy (DCM) is unknown. Cardiovascular magnetic resonance (CMR) allows accurate and reproducible measurement of LAV. We sought to determine the long‐term prognostic significance of LAV assessed by CMR in DCM. Methods and results We measured LAV indexed to body surface area (LAVi) in 483 consecutive DCM patients referred for CMR. Patients were prospectively followed up for a primary endpoint of all‐cause mortality or cardiac transplantation. During a median follow‐up of 5.3 years, 75 patients died and 9 underwent cardiac transplantation. After adjustment for established risk factors, LAVi was an independent predictor of the primary endpoint [hazard ratio (HR) per 10 mL/m2 1.08; 95% confidence interval (CI) 1.01–1.15; P = 0.022]. LAVi was also independently associated with the secondary composite endpoints of cardiovascular mortality or cardiac transplantation (HR per 10 mL/m2 1.11; 95% CI 1.04–1.19; P = 0.003), and HF death, HF hospitalization, or cardiac transplantation (HR per 10 mL/m2 1.11; 95% CI 1.04–1.18; P = 0.001). The optimal LAVi cut‐off value for predicting the primary endpoint was 72 mL/m2. Patients with LAVi >72 mL/m2 had a three‐fold elevated risk of death or transplantation (HR 3.00; 95% CI 1.92–4.70; P < 0.001). LAVi provided incremental prognostic value for the prediction of transplant‐free survival (net reclassification improvement 0.17; 95% CI 0.05–0.29; P = 0.002). Conclusions LAVi is a powerful independent predictor of transplant‐free survival and HF outcomes in DCM. Assessment of LAV improves risk stratification in DCM and should be incorporated into routine CMR examination.